The Influence of Cash Pick Up, Promotion and Cross-selling to Trust and Saving Decision: (Study on Customers using Micro National Savings Products at Panin Bank Sub Branch Office Kenjeran Surabaya City) - Modis April Shela; I Gede Arimbawa (Journal of World Conference (JWC), 2019)
The purpose of this study is to analyze the influence of cash pick up, promotion, and cross-selling to trust and saving decision in Panin Bank sub branch office Kenjeran Surabaya city. Research methods used in this study was the quantitative approach. The sample in this research is as many as 100 people of the total National Savings customer Micro (TAMI) Panin Bank Sub branch Kenjeran, with technique insindental sampling, and collection data techniques with the use of a questionnaire. In this study researchers using the technique of data analysis using PLS SmartPLS 3 software Partial Least Square. The results of this study found that cash pick up, promotions, and cross-selling a positive and influence against trust and saving decision in Panin Bank sub branch office Kenjeran with variable promotions need to be a particular concern by Panin Bank, because influential directly or indirectly against trust and saving decisions